Nigerian Cases in Business Management - Onah, Julius O.; Ejiofor, Pita N. O. (London : Cassell, 1978)
The case studies present in this book depict graphically the problems associated with owning and managing various indigenous business concerns ranging from baking, building, and printing, to petty trading and catering. It highlights problems associated with running a business far away from one's home, crises of succession, poor education, expatriate domination, management of resources, and some of the opportunities and disillusionments brought about by the Nigerian Civil War. The case studies presented in the book illustrate the speed with which changes are taking place in the Nigerian economy.
Bibliography: p. 136.
ne 4/04/2018
Loan
Keywords: Industrial management; Business enterprises